Procyanidins Extracted from the Lotus Seedpod Ameliorate Cognitive Impairment through CREB-BDNF Pathway Mediated LTP in APP/PS1 Transgenic Mice - Wang, Ziping; Li, Xiaolong; Ren, Xiaotong; Zhao, Siqi; Chen, Wenwen; Fan, Cheng; Xu, Yangliu; Pi, Xuejiao; Zhang, Yidan; Wang, Ting; Rong, Shuang (Current Pharmaceutical Biotechnology, 2023)
Background: Alzheimer’s disease (AD) is an age-related neurodegenerative disease and is featured by cognitive impairment. Procyanidins have been shown to have a potential protective effect against neurodegenerative diseases, but the underlying mechanism is not comprehensive enough. Objective: To further investigate the effects of procyanidins from lotus seedpod (LSPC) on cognition in AD. Methods: The APP/PS1 transgenic mice were administered with LSPC (100 mg/kg body weight) for five months. The Morris water maze test was used to assess learning and memory function, the long-term potentiation (LTP) was measured, and the expressions of Aβ, pCREB/CREB and BDNF were quantified by western blot. Results: LSPC significantly ameliorated cognitive dysfunction, reduced Aβ deposition and reversed the remarkable reduction of the phosphorylation of CREB and the expression of BDNF, and then enhanced the effect of LTP in APP/PS1 mice. Conclusion: These results revealed that LSPC could ameliorate cognitive impairment through the CREB-BDNF pathway that mediates the enhancement of LTP in APP/PS1 transgenic mice.
Keywords: APP/PS1